Geological and geomorphological controls on groundwater occurrence in a hard rock region - Rajaveni, S.P.; Brindha, Karthikeyan; Elango, L. (Springer, 2017)
Remote sensing and GIS tools have broadly helped hydrogeologists to delineate the groundwater prospective zones for watershed development and management. The origin, movement and existence of groundwater depends on several factors such as slope, drainage density, land use, geology, lineament density and geomorphology. Based on these, the mapping and identification of groundwater potential zones were carried out in a part of Nalgonda district, Telangana, India. The regions were categorised as high, moderate and low groundwater potential, and they were validated with the groundwater levels and yield of wells located in the corresponding zones. Extensive possibility for watershed development is possible in 41 % of the total 724 km2 and 46 % of the area offers moderate options. Any groundwater management project implemented in these favourable areas will bring maximum benefit. Similar studies should be considered necessary before designing a water resource development activity as it will reduce the cost on detailed field visits which are time-consuming.